What is a learning town? Reflections on the experience at Wirksworth - Wiltshier, Peter (TeMA - Journal of Land Use, Mobility and Environment, 2017)
This paper explores the legacy of regeneration project work and knowledge management and transfer as a result of intervention through a charity designed to support new business opportunities, specifically in arts and entertainment, tourism, skills development and training. As part of the University of Derby’s own work-related learning and problem-based learning, a project team was assigned to work alongside the charity ‘New Opportunities in Wirksworth!’ (NOW!). A participant observation, action research approach has been used to elicit and analyse the knowledge transfer, both explicit and implicit. Staff and students from the University of Derby have been contracted to research tourism development specifically in festival supply and demand, the attractiveness of the destination and its key features the market, mining heritage and volunteer railway. Staff and students also committed to an events strategy, marketing the destination and finance for start-ups. The University is engaged in tacit and explicit knowledge transfers. Key stakeholders have reflected on a decade of achievements and both fails and success stories. Agendas for the future have been identified and the project NOW! Has a legacy of both tacit and explicit knowledge for the benefit of other communities. There is an ongoing desire to explore how both public and private sectors can benefit from knowledge sharing and to benefit ongoing problem-based learning in education and training.